Achieving Synergy in the Russian Arctic: a Programme-Objective Approach. Issue 1 (September 2020) - Didenko, N I; Sheykina, A
Abstract: The sustainable development of Russian Arctic requires new approaches to the planning and organisation of government initiatives. In this article, we discuss the Arctic region in terms of a system of interconnected elements (subareas), each having its specific development goals and features. The subareas of the Russian Arctic are classified into 7 types according their characteristics. A synergistic basis for sustainable development is formed by the combination of subareas' development goals into a comprehensive programme using a programme-objective method. A development programme for the Arctic subareas based on a tree structure is advanced and possible development goals identified. It is concluded that a synergistic effect can be created by connecting Arctic subareas with each other in order to facilitate mutually beneficial interaction. A classification of the Arctic region according to its analytical decomposition in accordance with its specific functions and features is proposed. Types of subareas are: a) main towns – urban areas having a population of at least 1000 people having various infrastructure, buildings and structures; b) settlements; c) mineral and fossil fuel deposits; d) recreational areas and tourist attractions; e) fishing and reindeer herding areas; f) Northern Sea Route (NSR); g) objects of civil protection.